RESEARCH BOOTCAMP STATE UNIVERSITY OF JAKARTA WITH UNIVERSITY MALAYSIA SABAH IN ACCESSING INDEXED JOURNALS, PARAPHRASING, GRAMMAR CHECKING, AND REFERENCE MANAGEMENT - Sumiati, Ati; Pratama, Aditya; Puruwita, Dita; Zahra, Siti Fatimah; Andy, Andy; Armeliza, Diah; Yusuf, Muhammad; Syalsabila, Anis; Mufidah, Chusnanik; Maharani, Diva (International Journal of Engagement and Empowerment (IJE2), 2024)
Higher education institutions are under increasing pressure to produce globally competitive graduates by significantly increasing their research output and scientific publications, thus strengthening and enhancing their academic reputation and social impact. Yet, lecturers and students at the service location must gain skills in research-supporting software, scientific writing, and literature searching. Therefore, the State University of Jakarta and the University Malaysia Sabah jointly organize a research boot camp to address the rising demand for research competence and international publications in higher education by equipping participants with essential research skills. The Research Bootcamp Training aims to enhance research competency among students by providing online training in accessing indexed journals, paraphrasing, grammar checking, and reference management using relevant software. This program seeks to assist students at partner institutions in writing and publishing academic articles. With this activity, more students can publish their scientific work in national and international journals indexed by Scopus and Web of Science, thus improving the quality of research in Indonesia. In addition, this activity is expected to encourage the birth of a generation of young researchers who are productive and able to produce quality scientific works relevant to current problems